An Experimental Investigation of Diesel Engine Fuelled with MgO Nano Additive Biodiesel - Diesel Blends - C, Vijayakumar; A, Murugesan; D, Subramaniam; N, Panneerselvam (Bulletin of Scientific Research, 2019)
In this experimental investigation compacts the performance and emissions of compression ignition engines fuelled with MgO nano additive, maducaindica bio diesel blends were examined. Based upon the previous literatures only 20% mahuca methyl ester fuel blends without nano additives is suitable for compression ignition engine without affecting engine efficiency and its characteristics. In this paper magnesium oxide nano additives are added into the 40% Mahucaindica biodiesel- diesel blends at the rate of 50ppm for developing the test fuels. In this nano additives improve the properties of diesel fuel like viscosity, calorific value and decreased the flash point and fire point. Then compared the performance and emissions differences of all blended fuels used as a fuel in a diesel engine. The observation of results, 40MgO + 50ppm blended fuels brake thermal efficiency is improved then CO, HC, CO2and smoke decreased compared to other fuel blends. The results are taken into account, a blend of 40MgO+ Mgo50ppm is the best blend ratio compared than other blends with nano additives.